Intro to Rust (O'Reilly Media, 2019)
"Rust is a systems programming language that runs blazingly fast, prevents segfaults, and guarantees thread safety. Nathan Stocks (GitHub) leads a fast-paced introduction to Rust concepts, features, community, and language fundamentals. It's a crash course in why Rust is awesome and how to use some of the awesomeness. You'll learn how to create, compile, and run your own simple Rust project, familiarize yourself with the long list of Rust features, understand some of Rust's strength's and weaknesses, discover the current state of the Rust community, and explore the ownership system's three parts, If you've thought about getting into low-level systems programming, join in. ownership, borrowing, and lifetimes."--Resource description page